Media activism on and off line by Italian adolescents and young adults - Capobianco, Amelia <1973> (Alma Mater Studiorum - Università di Bologna, 2014)
From several researchers it appears that Italian adolescents and young people are grown up with commercial television which is accused to contain too much violence, sex, reality shows, advertising, cartoons which are watched from 1 to 4 hours daily. Adolescents are also great users of mobile phones and spend a lot of time to use it. Their academic results are below the average of Ocse States. However the widespread use of communication technology and social networks display also another side of adolescents who engage in media activism and political movement such as Ammazzateci tutti!, Indymedia, Movimento 5 Stelle, Movimento No Tav. In which way does the world economic crisis -with the specific problems of Italy as the cutting founds for school, academic research and welfare, the corruption of political class, mafia and camorra organisation induce a reaction in our adolescents and young people? Several researches inform us about their use of internet in terms of spending time but, more important, how internet, and the web 2.0, could be an instrument for their reaction? What do they do online? How they do it? Which is the meaning of their presence online? And, has their online activity a continuity offline? The research aims are: 1. Trough a participant observation of Social Network profiles opened by 10 young active citizens, I would seek to understand which kind of social or political activities they engage in online as individuals and which is the meaning of their presence online. 2. To observe and understand if adolescents and young people have a continuity of their socio-political engagement online in offline activities and which kind of experiences it is. 3. Try to comprehend which was (or which were) the significant, learning experiences that convinced them about the potential of the web as tool for their activism. === All’origine di questa ricerca ci sono due affermazioni, la prima di Al Gore, premio Nobel per la pace nel 2007, ha affermato che “La primavera araba ha avuto internet come strumento” La seconda è di Jacques Gonnet membro del gruppo di studio francese Clemì: “… [esiste un] legame fondamentale tra democrazia ed educazione ai media: (…). La scuola, luogo d’iniziazione ai valori di una società, si inscrive e si rivela, grazie ai media, in una visione politica del mondo. L’educazione ai media diventa un’iniziazione alle pratiche democratiche, (…)” La dichiarazione di Gore mi ha indotta a riflettere sull’attivismo dei giovani italiani, a fenomeni quali “Ammazzateci tutti!”, “Indymedia”, “Movimento 5 Stelle” “Libera” il Movimento “No Tav” ecc. Quella di J. Gonnet su quali possono essere le esperienze formative relative ai media per i giovani italiani. La scuola? La famiglia? I pari? Tutte queste? Altre?